Memórias do ensino de História - Experiências vividas na licenciatura da FAFICE/UECE (1966 A 1982): mitos, rótulos e contradições - Timbó, Isaíde Bandeira (2004)
This paper presents a reflection about the teaching formation in the degree course in History of FAFICE during the military dictatorship (...)